Postirradiation pulmonary fibrosis complicated by aspergilloma and bronchocentric granulomatosis. - Makker, H (1989)
An asthmatic patient requiring corticosteroid treatment developed a pulmonary aspergilloma in an area of postmastectomy radiation fibrosis. At necropsy bronchocentric granulomatosis was also found.